Economy and justice: A conflict without resolution? - Christian Hecker; Hans G. Nutzinger (Management Revue, 2010)
Problems of justice, such as high managerial salaries or the introduction of minimum wages, today arouse a lot of public attention and debate. This hints at the general fact that 'justice' cannot be reduced to mere efficiency questions as economists very often tend to assume. Therefore, this paper deals with opportunities to include aspects of social justice in economic analyses. The authors describe the historical development from the Aristotelian concept of justice (which includes both iustitia commutativa and iustitia distributiva) via the medieval idea of pretium iustum towards the classical liberal approach of Adam Smith (which excludes almost all aspects of distributive justice from the analysis of economic problems). The 'social question' in the 19th century revealed the limits of classical liberalism; nevertheless, the vision of increasing 'wealth of nations' became true for most market-oriented economies during the 20th century. But problems of poverty remained, especially for many countries of the South, but also for some strata of the population in successful market economies. Therefore, the limits of a pure liberal concept of justice even in modern market societies are revealed which in turn indicate the necessity of an integrated approach that applies the instruments of contemporary economics, but also allows for the restrictions of the liberal point of view. In contrast to present-day neo-liberalism, the approach of 'ordoliberalism', originated by Walter Eucken, which distinguishes between the 'frame order' of an economy and the economic process itself offers various opportunities to deal with current questions of justice, e.g. in the field of climate protection or in the issue of minimum wages, in a way which combines elements of justice with prerequisites of economic efficiency. These examples are discussed at the end of the paper.
Keywords: 650; Aristotelian concept of justice; pretium iustum; liberalism; neo-liberalism; ordo-liberalism; social question; climate protection; problems of poverty; integration of justice issues